Assimilating Critical Discourse Analysis and Debating Technique to Familiarize Students with the Use of HOTS in the Classroom - Istiqlaliah Nurul Hidayati; Abdul Rosyid; Entis Sutisna (Pedagonal : Jurnal Ilmiah Pendidikan, 2021)
Higher Order Thinking Skills (HOTS) are not only criteria of making test items for students, they also have to be implemented in daily basis especially in the teaching and learning process. Students can use the skills when they are familiar with them. In order to make the students familiar with the use of HOTS in the classroom, the researcher assimilates critical discourse analysis (CDA) and debating technique to foster the students’ ability in using their HOT skills. The use of the skills is seen from the activities of analyzing, evaluating, and creating that are done through the implementation of CDA and debate technique. Technology is also used here since the students have to enrich their knowledge on the motion debated by searching some relevant issues online. The sample of the research is 32 students of the fourth semester who are studying speaking skill in the English Education Study Program of Pakuan University. The research shows that the assimilation of CDA and debate technique can make the students familiar with the use of higher order thinking skills which are analyzing, evaluating, and creating. This paper suggests that teachers should use the assimilation to foster students’ use of HOTS.